2018
DOI: 10.1016/j.cca.2018.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neutrophil gelatinase-associated lipocalin and risk of cardiovascular disease: Findings from the PREVEND prospective cohort study

Abstract: Evidence suggests a non-linear association between NGAL and CVD risk, which is dependent on inflammation and renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, when we additionally adjusted our Cox proportional hazards regression models for eGFR at baseline, statistically significant relationships were abrogated. This is in line with other studies showing kidney function-dependency of NGAL concentrations across different patient populations [40][41][42]. The intimate relationship between NGAL levels and eGFR is sustained by studies that have shown that NGAL may represent a reliable biomarker of the severity of renal impairment, i.e., could represent a surrogate marker of kidney damage [11,43,44].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, when we additionally adjusted our Cox proportional hazards regression models for eGFR at baseline, statistically significant relationships were abrogated. This is in line with other studies showing kidney function-dependency of NGAL concentrations across different patient populations [40][41][42]. The intimate relationship between NGAL levels and eGFR is sustained by studies that have shown that NGAL may represent a reliable biomarker of the severity of renal impairment, i.e., could represent a surrogate marker of kidney damage [11,43,44].…”
Section: Discussionsupporting
confidence: 90%
“…25 Besides, neutrophil gelatinase associated lipocalin (NGAL) which is a 25 kDa protein that attach the granulocytes, it correlated with drug induced AKI since; it is responsible for the renal inflammation during ischemia thus; NGAL serum level be a sign of acute renal injury. 26 Additionally, different cytokines such as interleukin, interferon, and colony stimulating factors play an important and integral role in the renal tubular damage and repair so; they are considered as biomarkers of kidney injury during drug induced AKI. 27 Cystatin-c is a low molecular weight protein excreted by glomerular filtration and high level of Cystatin-c is linked with reduction of GFR and glomerular filtration.…”
Section: Biomarkers Of Acute Kidney Injurymentioning
confidence: 99%
“…Our study has a larger sample size and can therefore reveal the significant association between LCN-2 and stroke risk in the general population. In the Prevention of Renal and Vascular End-stage Disease study, a non-linear relationship was observed between LCN-2 and the risk of CVD, but LCN-2 was not associated with stroke in this study in Caucasians [ 23 ]. The apparent disagreement with our study may be related to population characteristics.…”
Section: Discussionmentioning
confidence: 88%